A Horse Story : Sami and Thomas Meet Pascal - McDonald, James (House of Lore Publishing, 2013)
On a visit to Grandma's, Sami and Thomas learn how to be good horse-sitters and in the process make a new friend in Pascal the horse. Cleaning the stall and brushing Pascal's shiny coat are just the beginning of this Sami and Thomas horse adventure.